Mid-arm muscle circumference: A significant factor of all-cause and cancer mortalities in individuals with elevated platelet-to-lymphocyte ratio. - Pi-Kai Chang; Wei-Liang Chen; Li-Wei Wu (PLoS ONE, 2018)
Platelet-to-lymphocyte ratio (PLR) is an inflammatory maker, and high PLR is associated with mortality in several diseases. The predictors of mortality in individuals with high PLR is still lacking. Our aims were to assess if mid-arm muscle circumference (MAMC) can predict all-cause mortality, cancer mortality, and cardiovascular mortality in individuals with high PLR. Adult participants from the National Health and Nutrition Examination Survey III (1988-1994) were included. All participants were divided into low PLR and high PLR groups with the cut-off point being the median PLR level, and each group was evaluated for risk factors of mortality. MAMC was divided into tertiles and the general characteristics of the study population related to MAMC were evaluated. The study included 14,221 adults with 6,701 (47.1%) male and 7,520 (52.9%) female participants. The median PLR ratio was 122. Higher levels of systolic blood pressure, total triglycerides, total cholesterol, low-density lipoprotein, C-reactive protein, uric acid, and glucose, as well as a higher age, were associated with increased risk of mortality in both groups. After adjusting for all the covariates, in the higher PLR group, the highest MAMC tertile was significantly associated with lower hazard ratios for all-cause and cancer mortalities compared with the lowest MAMC tertile. However, this association was not observed in the low PLR group. The highest MAMC tertile showed protective effects from all-cause and cancer mortalities compared with the lowest MAMC tertile in individuals with PLR ≥ 122. In conclusion, the highest MAMC tertile was significantly associated with decreasing HRs for all-cause and cancer mortalities compared with the lowest MAMC tertile in individuals with elevated PLR.